2021
DOI: 10.7860/jcdr/2021/48674.15213
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon High Resolution Computed Tomography Features of Pulmonary Tuberculosis: A Case Series

Abstract: Classical imaging manifestations of pulmonary Tuberculosis (TB) include consolidation, cavitation, necrotic mediastinal lymphadenopathy and pleural effusions. On the other hand, atypical imaging findings of pulmonary TB are sometimes encountered which create a diagnostic dilemma; three such patients are reported here. The predominant finding in the first patient (24-year-old female) was diffuse cystic lung disease with associated bilateral secondary spontaneous pneumothoraces. The subacute onset of symptoms, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…On the other hand, post-primary PTB takes place in already infected patients due to immunosuppression or malnutrition. 16 The present study showed that HRCT have The variation in values of diagnostic potential can be attributed to the epidemiological differences in PTB prevalence and risk factors. Another important reason can be the variation in scanning parameters of HRCT.…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand, post-primary PTB takes place in already infected patients due to immunosuppression or malnutrition. 16 The present study showed that HRCT have The variation in values of diagnostic potential can be attributed to the epidemiological differences in PTB prevalence and risk factors. Another important reason can be the variation in scanning parameters of HRCT.…”
Section: Discussionmentioning
confidence: 57%